math
simplify the expression

1. 2x = 3(x-2) - 3(x-6)

1. 2x + 12
2. 2x - 8 *****
3. 8x - 24
4. 2x - 24


2. C+6<-20

1. C < -26*******
2. C < -14
3. C < 26
4. C < 14



3. -5p > -30

1. P > 6
2. P < 6
3. P > -35
4. P < 35*****

4. -4 - 5(X+8)

1. -5x - 44
2. -5x + 36
3. -x - 8
4. -20x + 8*****

Respuesta :

Answer:

1. x=6

2. C <-26

3. p<6

4. -5x-44

Step-by-step explanation:

1. 2x = 3(x-2) - 3(x-6)

Distribute

2x= 3x-6 -3x+18

Combine like terms

2x =12

Divide by 2

2x/2 =12/2

x=6


2. C+6<-20

   Subtract 6 from each side

C+6-6 < -20-6

C <-26


3. -5p > -30  

Divide by -5.  Remember to flip the inequality when dividing by a negative

-5p/-5 < -30/-5

p<6


4. -4 - 5(X+8)

Distribute

-4 -5x-40

Combine like terms

-5x-44